2015
DOI: 10.1038/ajg.2015.101
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficacy of Sacral Nerve Stimulation in Slow Transit Constipation: A Two-Phase, Double-Blind Randomized Controlled Crossover Study

Abstract: In patients with refractory slow transit constipation, SNS did not improve the frequency of complete bowel movements over the 3-week active period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 38 publications
4
120
0
3
Order By: Relevance
“…Still, other studies used terms like “several years” . One study did not specify the duration of constipation . Constipation was described as severe in three studies, refractory in six, and intractable in three studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, other studies used terms like “several years” . One study did not specify the duration of constipation . Constipation was described as severe in three studies, refractory in six, and intractable in three studies …”
Section: Resultsmentioning
confidence: 99%
“…All studies described a failure of medical therapy such as laxatives, dietary modification, or biofeedback . Only two studies required patients to have failed a 4‐week run‐in period of medical therapy such as fiber, laxatives, enemas, and suppositories.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of SNS on colonic transit and rectal evacuation were only evaluated in a subset of patients; some parameters improved. By contrast, in a prospective, 18-week randomized, double-blind, placebo-controlled, two-phase crossover study, neither sub- nor supra-sensory SNS increased the proportion of complete bowel movements compared to sham SNS in 55 patients with medically-refractory slow transit constipation and normal anorectal functions evaluated with manometry, rectal balloon expulsion, and proctography 69 . Hence, although small studies suggest that SNS may improve rectal sensation in patients with DD and rectal hyposensitivity 70 and induce colonic propagating sequences 71 , there is no evidence that SNS improves bowel symptoms or rectal evacuation in defecatory disorders.…”
Section: Sacral Nerve Stimulation (Sns) For Defecatory Disordersmentioning
confidence: 76%
“…Recent randomized double-blind crossover studies have shown no difference between active and sham stimulations [17, 19]. In both studies, 30–60% of patients had a positive response during sham stimulation, suggestive of either lasting effects of sensory stimulation beyond washout period between sham and active treatment (2–3 weeks) or high placebo effects of this treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Suprasensory stimulation (a stimulation above sensory perception threshold) has been shown to increase colonic propagation which suggests the SNM affects afferent pathway modulation [16] although the precise mechanism is unclear. A recent randomized controlled trial by the same authors, however, showed no difference in the number of complete bowel movements between sham, subsensory and suprasensory stimulation [17]. Although it is likely that SNM modulates both local and central pathways, data to date are too sparse to allow a meaningful understanding of the association between the physiological findings and improvement of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%